Does Artificial Intelligence Improve Banking Financial Performance in Indonesia - Rochman Arif; Bandi, Bandi; Agung Nur Probohudono; Djuminah, Djuminah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to find empirical evidence of the influence of artificial intelligence (AI) on banking financial performance (ROA) and (ROE). The population in this study were banking companies in Indonesia totaling 66 banks during 2018-2023 and obtained observation data of 389 data. Hypothesis testing using panel data regression using the help of the STATA version 12 application. The results of the study show that the application of artificial intelligence (AI) has a positive and significant influence on financial performance both measured using (ROA) and (ROE).